Effects of increasing temperature due to aquatic climate change on the self-fertility and the sexual development of the hermaphrodite fish, Kryptolebias marmoratus - Park, Chang-Beom; Kim, Young Jun; Soyano, Kiyoshi (SPRINGER HEIDELBERG, 2017)
In order to assess the effects of increasing temperature on the reproductive performance of fish, different thermal conditions (i.e., 25.0, 26.5, 27.5, 28.5, 30.0 A degrees C) were used in this study and the self-fertilizing hermaphrodite fish, Kryptolebias marmoratus, was exposed to these different thermal conditions. During an exposure period of 30 to 150 days, the gonadosomatic index (GSI), gonadal development, the levels of plasma 17 beta-estradial (E2) and testosterone (T), hepatic vitellogenin (VTG) mRNA abundance, and the number of self-fertilized eggs were analyzed. This study confirmed that a high water temperature above 27.5 A degrees C led to the suppression of self-fertility of hermaphroditic fish from 30 days after exposure. The oocyte quality and maturation would be affected by the disruption of hepatic VTG synthesis at a high water temperature of 30 A degrees C, which resulted in the reduced the self-fertility in K. marmoratus. Consequently, this study suggests that elevated water temperature due to aquatic climate change prior to sexual maturation and the onset of spawning can lead to the reproductive dysfunction of hermaphroditic K. marmoratus.